IDDF2022-ABS-0196 The role of circulating tumor cells in peripheral blood as an adjunctive non-invasive diagnostic methods for colorectal cancer - Nursyirwan, Saskia Aziza; Noor, Dimas Ramadhian; Abdullah, Murdani; Jeo, Wifanto Saditya; Rahadiani, Nur; Handjari, Diah Rini; Fauzi, Achmad; Renaldi, Kaka; Maulahela, Hasan; Utari, Amanda Pitarini; Pribadi, Rabbinu Rangga; Muzellina, Virly Nanda; et al. (Gut, 2022)
BackgroundColorectal cancer (CRC) is one of the leading causes of cancer-related morbidity and mortality. The gold standard for diagnosing colorectal cancer is histopathology, which is obtained from a biopsy during colonoscopy. Since not all patients are willing to undergo invasive testing at the outset of the first diagnostic plan, new non-invasive approaches that can complement and enhance strategies for non-invasive diagnosis and management of colorectal cancer are urgently needed. Circulating tumor cells (CTC) in the blood are expected to be used as a non-invasive diagnostic marker in patients with CRC. This research is a diagnostic test of CTC on CRC using the isolation and analysis of the negative selection immunomagnetic method with Easysep™ and CD44 cancer mesenchymal marker.MethodsA cross-sectional study of adult patients with suspected colorectal cancer at Dr Cipto Mangunkusumo National General Hospital during September 2020 to September 2021. The diagnostic study analysis was used to find the cut-off point along with sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (PLR), and negative likelihood ratio (NLR) of CTC in detecting CRC.ResultsA total of 80 research subjects, the mean age was 56 ± 11 years. The proportion of subjects by gender was 46.3% female and 53.8% male patients. A total of 77.5% of the subjects had colorectal cancer, 7.5% had adenoma polyps, and 15% had inflammatory/hyperplastic polyps. The CTC diagnostic analysis to detect CRC (CRC compared with inflammatory/hyperplastic polyps + adenoma polyps), with a CTC cut-off point of > 1.5 cells/mL, showed that the sensitivity, specificity, PPV, NPV, PLR, NLR were 50%; 88.89%; 93.94%; 34.04%; 4.5; and 0.56, respectively. In addition, it was found that the cancer differentiation variable had a significant relationship (p<0.05) with the number of CTCs.ConclusionsCTC examination has low sensitivity and high specificity for diagnosing CRC. This examination can be considered as non-invasive diagnostic support for colorectal cancer before undergoing more invasive examinations, which are colonoscopy and histopathological biopsy.